97 An insight into the piglet’s microbial colonization evolution: From birth towards weaning - García, Mireia Saladrigas (J Anim Sci, 2020)
The aim of the present study was to explore the evolution of piglet gut microbiota from birth to weaning. Moreover, it was hypothesized that different farm environments could condition this process. Two farms, distinct in their use of antibiotics, and 10 litters per farm were selected. A total of 100 fecal samples were obtained from the same pig of each litter on d2, d7, d14 and d21 of lactation and d14 after weaning. The DNA was extracted by using the PSP® Spin Stool DNA Kit and sequencing of the 16S rRNA gene (V3-V4 region) performed by Illumina MiSeq Platform. Bioinformatics and biostatistical analysis were performed with QIIME and the open-source software R v3.5.3. (phyloseq package). Alpha diversity was strongly affected by age (P< 0.001), with an increasing richness of species through time. Beta diversity decreased after weaning (P< 0.001), suggesting a convergent evolution among individuals. Regarding the structure of the microbiota, a clear clustering of the samples according to age was observed (P< 0.001). A progressive decrease was observed as the piglets aged for Clostridiaceae, Enterobacteriaceae, Fusobacteriaceae, Pasteurellaceae and Streptococcaceae (P< 0.001). In contrast, Lachnospiraceae (P=0.003), Lactobacillaceae (P=0.003) and Veillonellaceae (P=0.025) increased along the d7–d14 period, but decreased afterwards. Campylobacteraceae, Erysipelotrichaceae, Ruminococcaceae (P< 0.001) and Prevotellaceae (P=0.005) gradually increased with age reflecting the change from a milk-oriented microbiome towards a butyrate-producing one. Regarding the impact of the farm, differences in species richness were found and also a distinct microbial structure (ANOSIM: P=0.025) associated to changes in some particular taxonomic groups. In conclusion, during the transition from birth to weaning, the pig microbiota showed a relevant succession of microbial groups towards a more stable ecosystem better adapted to the dry feed. In this relevant early-age process differences between farms seems to have a limited impact.